Provenance, clastic composition and their impact on diagenesis: A case study of the Oligocene sandstone in the Xihu sag, East China Sea Basin. (April 2021) - Wang, Wenguang; Lin, Chengyan; Zhang, Xianguo; Dong, Chunmei; Ren, Lihua; Lin, Jianli
Abstract: Sandstone composition, heavy mineral analysis, and bulk rock geochemistry analyses were used to investigate the provenance lithotypes and sediment transport pathways of the third, fourth, and fifth (E3h3, E3h4 and E3h5) members of the E3 h Formation at the gas–reservoir scale in the Xihu sag, East China Sea Basin. In addition, the diagenetic features and porosity of the metamorphic-sourced and volcanic-sourced sandstones were investigated. The provenance lithotypes of the E3h3, E3h4, and E3h5 were mainly medium–low grade metamorphic rocks and felsic to intermediate volcanic rocks. The sediment transport pathways were from northeast to southwest and from east to west, indicating that the E3h3, E3h4 and E3h5 members had two sediment provenance, namely, the metamorphic rocks of the northern Hupijiao Rise and the volcanic rocks of the eastern Diaoyudao Rise. Then the sedimentary microfacies distribution of the E3h3, E3h4, and E3h5 members and its relationship with the dual provenance sedimentary system were determined by using the heavy mineral assemblages, ZTR index, grain sizes, lithic fragments and quartz content. The initial porosity values of the metamorphic-sourced medium-grained and fine-grained sandstones were 35.35% and 35.22%, respectively; while the initial porosity values of the volcanic-sourced medium-grained and fine-grained sandstones were 34.09% and 34.97%, respectively. The average porosity compaction loss percentages were mainly 80.2% and 86.91% for the metamorphic-sourced medium–grained and fine–grained sandstones, and 86.95% and 87.23% for the volcanic-sourced medium–grained and fine–grained sandstones. The contact types of mineral grains in the metamorphic-sourced sandstones were mainly punctual, linear and concave-convex contacts; while the contact types of mineral grains in the volcanic-sourced sandstones were mainly linear, concave-convex, and sutured contacts. The metamorphic-sourced sandstone mainly developed chlorite coats; while the volcanic-sourced sandstones mainly contained pore-filling chlorite. The average quartz cement contents were 0.83% and 0.61% for the metamorphic-sourced medium–grained and fine–grained sandstones, and 0.67% and 0.43% for the volcanic-sourced medium–grained and fine–grained sandstones. The illite, mixed-layer illite/smectite and calcite cement reduced the sandstone porosity by filling pores. The metamorphic–sourced sandstones mainly developed primary intergranular pores and intergranular dissolved pores; while the volcanic–sourced sandstones mainly developed intergranular dissolved pores, intragranular dissolved pores, and moldic pores. The metamorphic-sourced sandstones had a higher porosity than the volcanic-sourced sandstones with the same grain size, which the difference in their porosities reached 1–3%. Highlights: Metamorphic and volcanic rock provenance at a gas-reservoir scale were determined. Sediment transport pathways were from northeast to southwest and from east to west. The compaction, chlorite and quartz cementation are related to provenance lithotype. The volcanic-sourced sandstones has strong compaction degree.